Clonal origin and development of high hyperdiploidy in childhood acute lymphoblastic leukaemia - Woodward, Eleanor L; Yang, Minjun; Moura-Castro, Larissa H; van den Bos, Hilda; Gunnarsson, Rebeqa; Olsson-Arvidsson, Linda; Spierings, Diana C J; Castor, Anders; Duployez, Nicolas; Zaliova, Marketa; Zuna, Jan; Johansson, Bertil; et al. (Nature communications, 2023)
High hyperdiploid acute lymphoblastic leukemia (HeH ALL), one of the most common childhood malignancies, is driven by nonrandom aneuploidy (abnormal chromosome numbers) mainly comprising chromosomal gains. In this study, we investigate how aneuploidy in HeH ALL arises. Single cell whole genome sequencing of 2847 cells from nine primary cases and one normal bone marrow reveals that HeH ALL generally display low chromosomal heterogeneity, indicating that they are not characterized by chromosomal instability and showing that aneuploidy-driven malignancies are not necessarily chromosomally heterogeneous. Furthermore, most chromosomal gains are present in all leukemic cells, suggesting that they arose early during leukemogenesis. Copy number data from 577 primary cases reveals selective pressures that were used for in silico modeling of aneuploidy development. This shows that the aneuploidy in HeH ALL likely arises by an initial tripolar mitosis in a diploid cell followed by clonal evolution, in line with a punctuated evolution model.
Keywords: chromozomální nestabilita; Diploidy; Precursor Cell Lymphoblastic Leukemia-Lymphoma; diploidie; lidé; akutní lymfatická leukemie; Chromosomal Instability; Aneuploidy; chromozomální aberace; aneuploidie; Chromosome Aberrations; Humans